2016
DOI: 10.1002/jbm.a.35783
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, characterization, and in vitro evaluation of silver‐containing arabinoxylan foams as antimicrobial wound dressing

Abstract: Arabinoxylan ferulate (AXF) foams were fabricated via enzymatic peroxidase/hydrogen peroxide crosslinking reaction followed by freeze-drying and studied as a potential wound dressing material. The AXF foam’s rheological, morphological, porous and swelling properties were examined. AXF foams were found to be a viscoelastic material that proved to be highly porous and water absorbent. AXF foams possessed low endotoxin levels and were cytocompatible with fibroblasts. Silver was successfully integrated into AXF fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…A similar behavior was reported by Samuelsen et al [46] where the treatment of AX from barley (0.5–3 mg/mL AX) had no significant effect on the proliferation of two human colon cancer cell lines, HT-29 and Caco-2. Moreover, in a previous study, AX foams prepared by peroxidase/H 2 O 2 enzymatic cross-linking reaction did not have a cytotoxic effect on NIH3T3 fibroblasts [67]. In that study, the cell viability values (~96%) were close to those observed in the non-cancerous cell line (CCD 841 CoN) treated with AXM, which was evaluated in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…A similar behavior was reported by Samuelsen et al [46] where the treatment of AX from barley (0.5–3 mg/mL AX) had no significant effect on the proliferation of two human colon cancer cell lines, HT-29 and Caco-2. Moreover, in a previous study, AX foams prepared by peroxidase/H 2 O 2 enzymatic cross-linking reaction did not have a cytotoxic effect on NIH3T3 fibroblasts [67]. In that study, the cell viability values (~96%) were close to those observed in the non-cancerous cell line (CCD 841 CoN) treated with AXM, which was evaluated in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…2d). The hydrogel's antibacterial properties could be attributed to the reversible Ag-S bond produced from crosslinking SH-PEG and AgNO 3 and the hydrogel's interaction with sulfur-containing proteins in the bacterial cell membrane 26,27 . The enhanced prevention of bacterial infections for wound healing was evident in the DFO-hydrogel's measured inhibition zone, which was larger in comparison to that of the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments revealed arabinoxylan hydrogels to have a two-and-a-half-fold increase in swelling when introduced into water [ 43 ]. Lyophilized arabinoxylan gels fabricated in our study have demonstrated swelling ratios above 20 after 48 h [ 44 ]. Arabinoxylan is an intriguing polysaccharide for hydrogel wound dressing formation because it does not require the use of toxic organic solvents but instead uses water instead for solubilizing before crosslinking.…”
Section: Fabrication Platforms Of Polysaccharides As Wound Dressinmentioning
confidence: 99%
“…The study showed complete dermal regeneration after implantation of dextran hydrogels compared to non-treated and treated control groups. Our group has developed lyophilized arabinoxylan hydrogels that exhibited viabilities above 96% on fibroblasts cultured in vitro [ 44 ]. The results concluded that fibroblasts that play a prominent role in the proliferative and remodeling stages of wound healing maintain their cytocompatibility after exposure to arabinoxylan.…”
Section: Biocompatibility Assessment Of Polysaccharides As Wound Dmentioning
confidence: 99%
See 1 more Smart Citation